2021
DOI: 10.1111/jmwh.13275
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Medications and Devices for the Care of Low‐Risk Childbearing Families: An Analysis of Existing Law and Strategies for Advocacy

Abstract: Limited access to medications and devices relevant to the care of low‐risk childbearing families acts as a barrier to the successful integration of high‐quality midwifery care into health care systems. Families who live in clinically underserved areas, whether urban or rural, are particularly in need of perinatal professionals who can provide comprehensive care. This article reviews existing US laws that impact whether families who choose community‐based care with direct entry midwives have access, through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Additionally, many states have regulations in place that limit the ability of midwives or other healthcare personnel to deliver vaccines. 21 Survey studies have demonstrated logistical, interprofessional and informational barriers to the certified nurse midwives or registered midwives providing vaccines. 22 If HBV is available at these locations, the freestanding birth center facilities may not have policies in place that prioritize the administration of HBV at the time of birth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many states have regulations in place that limit the ability of midwives or other healthcare personnel to deliver vaccines. 21 Survey studies have demonstrated logistical, interprofessional and informational barriers to the certified nurse midwives or registered midwives providing vaccines. 22 If HBV is available at these locations, the freestanding birth center facilities may not have policies in place that prioritize the administration of HBV at the time of birth.…”
Section: Discussionmentioning
confidence: 99%
“…In Washington state, LMs have been regulated by the Department of Health since 1917 and have one of the most integrated and comprehensive practice statutes in the United States. 14,27 Immigrant midwives educated abroad advocated for initial midwifery regulation and practiced under that law for many decades; the statute was then revitalized in the 1970s when community midwifery reemerged. 14 Legislative updates in the 1980s laid the groundwork for future changes as community needs and the standard of care evolved over time.…”
Section: Expanding Midwifery Practice In Washington Statementioning
confidence: 99%
“…14,27 Immigrant midwives educated abroad advocated for initial midwifery regulation and practiced under that law for many decades; the statute was then revitalized in the 1970s when community midwifery reemerged. 14 Legislative updates in the 1980s laid the groundwork for future changes as community needs and the standard of care evolved over time. Since that time, LMs have collaborated with legislators, community members, and other professional organizations to expand legal access to midwifery and to life-saving medications and devices.…”
Section: Expanding Midwifery Practice In Washington Statementioning
confidence: 99%
“…The country lacks a universal health care system that provides equitable insurance coverage for all birth settings 4 . Birth center and home birth options exist within an uneven network of state midwifery regulations and insurance reimbursement policies that largely do not guarantee coverage for people or payment to health care providers 33,34 . In addition, there are 1095 counties that are referred to as maternity care deserts , or areas in which there are extremely limited or no birth facilities or providers 35 .…”
Section: Shared Decision‐making In Birth Settingsmentioning
confidence: 99%
“…4 Birth center and home birth options exist within an uneven network of state midwifery regulations and insurance reimbursement policies that largely do not guarantee coverage for people or payment to health care providers. 33,34 In addition, there are 1095 counties that are referred to as maternity care deserts, or areas in which there are extremely limited or no birth facilities or providers. 35 Additional barriers to shared decision-making about birth settings include health care provider biases about birth center and home birth, [36][37][38] media bias and lack of knowledge about such options among the public, 39,40 and financial profits linked to patient numbers and cesarean birth.…”
Section: Shared Decision-making In Birth Settingsmentioning
confidence: 99%